2004
DOI: 10.1016/j.otohns.2003.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Drainage: Recommended as the Initial Approach for the Treatment of ParapHaryngeal Abscesses

Abstract: IOD is a safe and effective treatment for PPA in the pediatric population. It leads to decreased morbidity, shortened anesthesia time, and reduced economic burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 8 publications
0
41
0
2
Order By: Relevance
“…It is generally accepted that retropharyngeal abscesses can be safely drained intraorally. Some authors consider an intraoral approach as a reasonable initial method of management also for lateral pharyngeal space abscesses, if CT scan shows the abscess to be medial to the great vessels of the neck [13,14] . The intraoral approach is simpler, less aggressive (no risk of keloids and of injury to the marginal mandibular nerve) and it requires shorter recovery time than external approach.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that retropharyngeal abscesses can be safely drained intraorally. Some authors consider an intraoral approach as a reasonable initial method of management also for lateral pharyngeal space abscesses, if CT scan shows the abscess to be medial to the great vessels of the neck [13,14] . The intraoral approach is simpler, less aggressive (no risk of keloids and of injury to the marginal mandibular nerve) and it requires shorter recovery time than external approach.…”
Section: Discussionmentioning
confidence: 99%
“…Daya et al [12] preferred the intraoral approach for surgical drainage of infections of the retropharyngeal and parapharyngeal spaces unless the collection was lateral to the great vessels of the neck. Amar and Manoukian [13] compared intraoral drainage and external neck drainage in terms of duration of anesthesia, duration of postoperative intravenous antibiotics and length of postoperative hospital stay and concluded that intraoral drainage is a safe and effective initial treatment for parapharyngeal abscess in the pediatric population. However, abscesses located in the poststyloid compartment or that demonstrate extension to other spaces must be drained by the traditional transcervical approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition the transoral drainage had a shorter duration of admission than the transcervical drainage in our study. Furthermore the morbidity of transoral drainage is very low [6,13] . Rarely there are a few cases of pseudoaneurysm of the internal carotid artery related to parapharyngeal infection [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Oral and Maxillofacial surgery text book described the incision to be made in healthy skin and mucosa when possible in a normal skin fold: Dissect bluntly, place a drain, followed by drain removal when the drainage becomes less. 10 Intraoral incisions are only indicated in uncomplicated infections limited to the sublingual compartment; otherwise an external approach is recommended.…”
mentioning
confidence: 99%
“…A short incision drainage as described in the literature includes placing the incision in healthy mucosa or skin and in an esthetic area, if possible; obtaining gravity-dependent drainage; and performing blunt dissection during drainage to avoid damage to adjacent vital structures. 10 Long dissecting incisions and open dissection are usually not necessary, except perhaps in cases of necrotizing fasciitis or descending necrotizing mediastinitis, in which repeated surgical exploration, debridement, and drainage can be anticipated. Abscess, without question, requires incision and drainage, whereas the surgical management of cellulitis is more controversial.…”
mentioning
confidence: 99%